Acetylated Furostene Glycosides from Solanum gilo Fruits - Tchoupang, Edwige Nana; Reder, Christina; Ateba, Sylvin Benjamin; Zehl, Martin; Kählig, Hanspeter; Njamen, Dieudonné; Höller, Franziska; Glasl-Tazreiter, Sabine; Krenn, Liselotte (Planta Medica, 2017)
In continuation of our work on a traditional mixture of spices called “Nkui”, used in Cameroon for its influence on womenʼs reproductive health, we investigated the chemical composition of Solanum gilo, one component of “Nkui”. A methanolic extract was studied in detail. After dereplication of several known compounds, two furo-5-stene-derived saponin glycosides with acetylated sugar moieties were isolated. By extensive 1- and 2D NMR experiments and HR-MS and GC-MS methods, the structures were elucidated as 26-[(3‴,4‴,6‴-tri-O-acetyl)-β-D-glucopyranosyloxy]-22-hydroxyfurost-5-en-3β-yl-O-α-L-rhamnopyranosyl-(1″→2′)-β-D-glucopyranoside (A) and 26-[(3‴,4‴,6‴-tri-O-acetyl)-β-D-glucopyranosyloxy]-22-hydroxyfurost-5-en-3β-yl-[O-α-L-rhamnopyranosyl-(1′′′′→4′)-O-α-L-rhamnopyranosyl-(1″→2′)]-β-D-glucopyranoside (B), both new natural compounds.
Keywords: Solanum gilo Raddi; Solanum aethiopicum L.; Solanaceae; furostene-type glycosides; 26-[(3‴,4‴,6‴-tri-O-acetyl)-β-D-glucopyranosyloxy]-22-hydroxyfurost-; 5-en-3β-yl-O-α-L-rhamnopyranosyl-(1′′→2′)-β-D-glucopyranoside; 26-[(3‴,4‴,6‴-tri-O-acetyl)-β-D-glucopyranosyloxy]-22-hydroxyfurost-; 5-en-3β-yl-[O-α-L-rhamnopyranosyl-(1′′′′→4′)-O-; α-L-rhamnopyranosyl-(1″→2′)]-β-D-glucopyranoside